(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Permyakov O. A., Zelenkova N.I., Burman L.V. Formation of students’ creative abilities by means of new pedagogical technologies. In the article interpretation of the basic concept of the subject, analyzed the contains students creative faculty, means new pedagogical technological.